Entrepreneurship around the World--Before, During, and After the Crisis - Klapper, Leora; Meunier, Frederic; Diniz, Laura (World Bank Group, Washington, DC, 2015)
The 2014 World Bank entrepreneurship database provides a unique indicator of new business registration, allowing the measurement of entrepreneurial activity across economies and over time. The most recent data show that by 2012, only 56 percent of economies around the world had reached the level of new firm creation that they had achieved before the global financial crisis hit in 2007. The pace of new firm creation has been slightly stronger in developing than in developed economies. And the share of economies with year-on-year growth in the rate of firm creation is now higher in the developing than in the developed world.